2020
DOI: 10.3748/wjg.v26.i41.6488
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of non-pharmacological interventions for irritable bowel syndrome in adults

Abstract: BACKGROUND Although nonpharmacological interventions (NPI) for irritable bowel syndrome (IBS) have been applied clinically, their relative efficacy and safety are poorly understood. AIM To compare and rank different NPI in the treatment of IBS. METHODS Five electronic databases were searched from their inception to January 12, 2020. Data of included publications were analyzed using network meta-analysis (NMA). Quality of endpoints were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…Our exploratory meta-analysis reported similar results to a recent network meta-analysis [53] regarding the effectiveness and safety of non-pharmacological interventions for IBS symptoms. Although the scope of this paper was different from our study (it included also diet modifications and dietary complements such as probiotics), this study confirmed the potential effectiveness of acupuncture.…”
Section: Discussionsupporting
confidence: 83%
“…Our exploratory meta-analysis reported similar results to a recent network meta-analysis [53] regarding the effectiveness and safety of non-pharmacological interventions for IBS symptoms. Although the scope of this paper was different from our study (it included also diet modifications and dietary complements such as probiotics), this study confirmed the potential effectiveness of acupuncture.…”
Section: Discussionsupporting
confidence: 83%
“…Treatment of IBS focuses on symptom management to maintain daily functioning and improve QOL. However, due to significant side effects of prescribed medications, some sufferers do not take multiple CM but instead turn to complementary and alternative therapies for remedy [ 11 , 29 ]. A number of SRs/MAs have investigated the efficacy of acupuncture for IBS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with routine pharmacotherapies and placebo, acupuncture and cognitive-behavioral therapy (CBT) had better efficacy in relieving IBS symptoms. Based on the SUCRA values, acupuncture ranked first in improving overall clinical efficacy and avoiding adverse effects [22]. Acupuncture produced a more significant effect than loperamide in weekly defecation.…”
Section: Discussionmentioning
confidence: 99%